The Relationship between Students’ Arabic Language Learning Outcomes and Their Qur’anic Memorization (Tahfiz) Ability - Dari, Tiara Wulan; Halomoan (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the statistical relationship between students’ Arabic language learning outcomes and their Qur’anic memorization (tahfiz) ability in an integrated Islamic junior secondary school context. The research seeks to empirically validate the theoretical assumption that linguistic mastery, particularly semantic comprehension of Arabic, contributes to the effectiveness of Qur’anic memorization. This study employed a quantitative correlational design involving 100 ninth-grade students selected through simple random sampling from a population of 132 students. Arabic language learning outcomes were obtained from official semester examination records, while tahfiz ability was measured using a validated instrument assessing tajwid accuracy, fluency, fashahah, and recitation manners. Instrument reliability testing yielded a Cronbach’s Alpha coefficient of 0.866, indicating high internal consistency. Data were analyzed using descriptive statistics, Pearson Product Moment correlation, and simple linear regression, preceded by normality and linearity tests. The findings indicate that Arabic learning outcomes were categorized as high (M = 97.68), whereas Qur’anic memorization ability was categorized as moderate (M = 84.58). Pearson correlation analysis revealed a positive and statistically significant relationship between Arabic achievement and tahfiz ability (r = 0.202, p = 0.044). However, the effect size was small, with Arabic learning outcomes explaining approximately 4.1 percent of the variance in memorization performance. Regression analysis confirmed that Arabic achievement positively predicts tahfiz ability. This study contributes novel empirical evidence by quantitatively examining the relationship between Arabic academic achievement and Qur’anic memorization ability at the junior secondary level within an integrated Islamic schooling framework. Unlike previous studies that primarily focus on pedagogical strategies or qualitative insights, this research statistically measures the cognitive-linguistic linkage between Arabic mastery and tahfiz performance. The study theoretically strengthens the integration of cognitive learning theory and Islamic education research by demonstrating that semantic comprehension supports memorization retention. Practically, it provides evidence-based insights for curriculum integration, suggesting that enhancing Arabic proficiency should be aligned with structured tahfiz programs, motivational reinforcement, and systematic repetition strategies to optimize memorization outcomes.